Formulating Infostructure Maturity Model for Disaster Management - Latif A.A.; Arshad N.H.; Janom N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Disaster prevention; Error statistics; Software engineering; Assessment tool; Capability maturity models; Disaster management; Evaluation tool; Maturity levels; Maturity model; Process maturity; Standard errors; Disasters